Atitudes da comunidade acadêmica da Universidade Federal do Ceará em relação à inclusão de alunos com deficiência - Maciel, Antônia Kátia Soares (2014)
This paper addresses the inclusion of students with disabilities in Higher Education Institutions (HEIs), taking as its object of study the social attitudes of teachers, students and employees of the Federal University of Ceará (UFC). The overall objective of the research is to investigate the social attitudes of the academic community of UFC regarding the inclusion of students with disabilities and specific objectives are: to verify how the social atitudes in the academic comunity of UFC are presented and to observe the differences these social attitudes among the courses surveyed. The research is quantitative and qualitative nature and use as an instrument of data collection Lickert Scale of Social Attitudes Toward Inclusion (ELASI) in the form A. The study included students, faculty and staff of the UFC, a total of 322 respondents the ELASI, divided between seven courses of Campi Fortress UFC, considering the presence of students with disabilities and the different areas of knowledge of each course. 5 undergraduate courses were selected for the research - Bachelor of Physical Education; Environmental Sciences (both courses have no students with disabilities enrolled); Letters-Portuguese Literature (with two students with disabilities: one with physical disabilities and other with deafness); Librarianship (with a student with multiple disabilities - low vision and disability / wheelchair user); and Computation (with 5 students with disabilities, low vision with 3 and 2 with disabilities) - 2 courses and Postgraduate: Masters in Psychology (with a student with blindness) and MSc in Chemistry (with a student with physical disabilities) . The results show that most of the courses studied had more favorable social attitudes toward inclusion of students with disabilities. However, no significant difference between the course of Computer comparing the following courses: Bachelor of Physical Education; Letters-Portuguese Literature; Masters Degree in Psychology and a Masters in Chemistry. It is noticed that the social attitudes of the respondents of the course Computer are less favorable compared to these courses mentioned, ie, the presence of students with disabilities in the course of Computer did not influence the participants more positive attitudes, as well as the area of knowledge this seems to favor more positive social attitudes, it is a course in the exact sciences and there is discussion about accessibility and inclusion of students with disabilities. Other differences were constadas between courses of Environmental Sciences and Master in Psychology, being the second most favorable social attitudes toward inclusion of students with disabilities and the comparison between the courses of Librarianship and Master in Psychology, in which attitudes social respondents of the Master in Psychology are more inclusive. However, it is considered that the social attitudes of the academic community of the UFC in general are more favorable toward inclusion, but in some courses surveyed there is a need for change more positive attitudes toward inclusion of students with disabilities.